Pediatric schwannoma of the hypoglossal nerve: a case report and narrative literature overview - Marcandella, Elena Sofia; Boscarelli, Alessandro; Murru, Flora-Maria; Abbracciavento, Giuseppe; Spazzapan, Peter; Schleef, Jurgen (Frontiers in Oncology, 2024)
Schwannomas are benign, slow-growing tumors originating from the Schwann cells of nerve sheaths. Extracranial schwannomas are rare, particularly in pediatric populations. Here, we report the case of a hypoglossal schwannoma in a 15-year-old male who experienced tongue paresthesia and fasciculations and difficulty swallowing two years before hospital admission. Magnetic resonance imaging showed an oval mass with sharp and regular limits of approximately 45 × 29 × 25 mm in the cranial portion of the right carotid adipose space, caudal to the right carotid and lateral foramen. The patient underwent surgery, and a histological examination confirmed a schwannoma of the hypoglossal nerve. Six months after surgery, the patient was symptom-free. The literature on schwannomas of the hypoglossal nerve is scarce, with only a few previously reported cases in the adult population. Despite their rarity, schwannomas should be considered in the differential diagnosis of masses located in the neck that present with lingual and occasionally auditory symptoms, even in pediatric patients. Surgical resection is recommended and has a low risk of long-term recurrence.